Multi-Layered High Permeability Conduits Connecting Onshore and Offshore Coastal Aquifers - Weymer, Bradley A.; Wernette, Phillipe A.; Everett, Mark E.; Pondthai, Potpreecha; Jegen, Marion; Micallef, Aaron (Frontiers in Marine Science, 2020)
Groundwater resources in coastal regions are facing enormous pressure caused by population growth and climate change. Few studies have investigated whether offshore freshened groundwater systems are connected with terrestrial aquifers recharged by meteoric water, or paleo-groundwater systems that are no longer associated with terrestrial aquifers. Distinguishing between the two has important implications for potential extraction to alleviate water stress for many coastal communities, yet very little is known about these connections, mainly because it is difficult to acquire continuous subsurface information across the coastal transition zone. This study presents a first attempt to bridge this gap by combining three complementary near-surface electromagnetic methods to image groundwater pathways within braided alluvial gravels along the Canterbury coast, South Island, New Zealand. We show that collocated electromagnetic induction, ground penetrating radar, and transient electromagnetic measurements, which are sensitive to electrical contrasts between fresh (low conductivity) and saline (high conductivity) groundwater, adequately characterize hydrogeologic variations beneath a mixed sand gravel beach in close proximity to the Ashburton River mouth. The combined measurements - providing information at three different depths of investigation and resolution - show several conductive zones that are correlated with spatial variations in subsurface hydrogeology. We interpret the conductive zones as high permeability conduits corresponding to lenses of well-sorted gravels and secondary channel fill deposits within the braided river deposit architecture. The geophysical surveys provide the basis for a discharge model that fits our observations, namely that there is evidence of a multilayered system focusing groundwater flow through stacked high permeability gravel layers analogous to a subterranean river network. Coincident geophysical surveys in a region further offshore indicate the presence of a large, newly discovered freshened groundwater system, suggesting that the offshore system in the Canterbury Bight is connected with the terrestrial aquifer system.